Los presbiterianos revolucionarios en Yucatán. Inserción social y participación política - May May, Ezer R. (El Colegio de México, A.C., 2018)
This article analyzes and describes the Protestant experience in Yucatán at the beginning of the 20th Century, focusing on the arrival and establishment of Protestantism in the city of Mérida. Later, it explores the political participation of Presbyterians in the government of Salvador Alvarado, as well as how this was perceived. This episode is complemented with an analysis of incidents related to Presbyterians on haciendas. Through a study of the archives of the State of Yucatán, the Archbishop of Yucatán and the local liberal and conservative periodical archives, as well as those of the Presbyterian Church, it examines the differences and similarities between Presbyterianism in Yucatán and central Mexico with the goal of contributing to a better understanding of the relationship between religion and politics in general and between Protestantism and the Mexican Revolution in particular.